Turnaround time for the provision of packed red cells (PRC) and factors affecting their achievements in the Blood Transfusion Unit of Dr. Sardjito General Hospital, Yogyakarta - Kaslam, Surawijaya Bakhtiar; Sukorini, Usi; Triyono, Teguh (Universitas Gadjah Mada, 2023)
Turnaround time (TAT) is defined as the time it takes since request/sample is received at the blood bank until blood is cross-matched/reserved and available for transfusion. Turnround time prolongation affects patient care and satisfaction. This study aimed to evaluate TAT for the provision of packed red cells (PRC) at the Blood Transfusion Unit of Dr. Sardjito General Hospital, Yogyakarta, analyze factors affected in TAT prolongation, and provide solution the prolongation. It was an analytical descriptive study with a qualitative design, by calculating the time since receipt of the PRC request at the Blood Transfusion Unit or since blood collection from donors until data input of the crossmatch results in Dr. Sardjito General Hospital management information system (SIMETRIS) completed. Moreover, the delay in the provision of PRC at the Blood Transfusion Unit was also analyzed. There were 3 (1.5%) of 200 ER samples that met TAT for the provision of the PRC, which was 30 min after receipt of the request at the Blood Transfusion Unit in cito conditions. There were 20 (10%) of 200 samples from the wards that met TAT for the provision of the PRC, which was 2 h after receipt of the request at the Blood Transfusion Unit if the blood stock was available. There were 55 (27.5%) of 200 samples from the wards that met TAT for the provision of the PRC, which was 4 h after the blood was collected from the donor. TAT for the provision of the PRC at the Blood Transfusion for the available blood stock group was 179.08 (67.2 – 396.27) min, replacement blood donor group was 485.38 (126.43 – 910.68) min, and cito group was 121.29 (27.68 – 421.38) min. In conclusion, there is TAT prolongation of PRC provision at the Blood Transfusion Unit of Dr. Sardjito General Hospital.